PENGARUH SIMPANAN DAN PINJAMAN ANGGOTA KOPERASI TERHADAP SISA HASIL USAHA - Siska; Husin; Fitriaman (Accounting Student Series on Emerging Trends, 2026)
This study aims to examine and determine the effect of Member Deposits and Loans on the Remaining Cooperative Business Results at the Savings and Loans Cooperative of the Women's Amanah Economic Institution. The type of research in this study is quantitative research. The data sources used are secondary data in the form of member deposit records, member loans and remaining operating results. The data collection method in this study used documentation. The research methods used are descriptive analysis methods and multiple linear regression analysis with the help of IBM SPSS Statistical Version 25 software application. The results of this study show that (1) Deposits of partial members have a significant and positive effect on the remaining operating results of the cooperative. (2) Member loans have a significant and partial positive effect on the remaining operating results. (3) Member deposits and member loans simultaneously or jointly have a significant and positive influence on the remaining operating results.